Incompatibilidad de caracteres como causal de divorcio - Pozo Pincay, Cipriano Juan (2021)
We have always been struck by the limitations on the freedom to decide of people when Divorce causes are tartare in Ecuadorian civil legislation. That is why, we draw as the theme of this work: "Proposal for reform to art. 110 of the Civil Code in the sense of proposing the incompatibility of characters as grounds for divorce”, in order to investigate the legal possibility that this grounds for divorce may be included in art. 11 0 of the Civil Code, and likewise, to demonstrate that it subsumes several of the causes, there, strictly related. In this sense, we set the following general objective: - Propose a legislative reform to art. 110 of the Civil Code, in the sense of including a new cause consisting of the incompatibility of characters and which, in turn, subsumes the grounds provided in art. 110, in the numerals so that divorce can be processed for this cause, thereby ensuring that the marriage union subsists whenever there is the will of both spouses to continue it, as a key feature of marriage as a contract.............